AN ANALYSIS OF CURRICULUM MANAGEMENT AND ITS IMPACT ON STUDENTS’ SPATIAL ABILITY - Putri Yulianti; Eka Putra (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study is motivated by the importance of students’ spatial abilities in supporting learning achievement, particularly in subjects that require visual understanding and spatial representation. Spatial ability is influenced not only by students’ cognitive factors but also by the effectiveness of curriculum management implemented in the learning process. This study aims to analyze the influence of curriculum management on students’ spatial abilities. The research employed a qualitative approach using the Systematic Literature Review (SLR) method. Data were collected from various relevant national and international journal articles and analyzed through identification, selection, evaluation, and synthesis stages. The findings indicate that effective curriculum management, including planning, implementation, and evaluation, plays a significant role in enhancing students’ spatial abilities. A well-structured and contextual curriculum promotes meaningful learning and supports the development of visualization skills and spatial understanding. Therefore, improving curriculum management is a crucial factor in enhancing both students’ spatial abilities and the overall quality of learning